Celebrity Endorsement Sebagai Pembentuk Brand Credibility Dan Consumer Based Brand Equity (Studi Pada Boyband BTS Pada Merek Samsung) - Santi Rimadias; Imam Fathur Rahman (MDP Student Conference, 2022)
Abstract: In today's digital and modern era, competition between mobile phone brands is increasing. Mobile phone brands compete to make various promotions to retain loyal users and new users. This study aims to examine and analyze the effect of Celebrity Endorsement BTS against Brand Credibility and Consumer-Based Brand Equity Samsung and influence Brand Credibility Samsung's Consumer-Based Brand Equity. This study uses descriptive analysis using a questionnaire as a research tool. The sample in this study is Samsung mobile phone users who are fans of the BTS Boyband. Research data was collected by distributing online questionnaires to 100 respondents. For data analysis and processing using Smart Partial Least Square (SmartPLS) 3. The results of the study explain that Celebrity Endorsement BTS has a positive effect on Samsung Brand Credibility, Samsung Brand Credibility has a positive effect on Consumer Based-Brand Equity, and Celebrity Endorsement BTS has no effect on Consumer Based-Brand Equity. Abstrak: Di era digital dan modern saat ini, persaingan antar merek ponsel semakin meningkat. Merek ponsel bersaing untuk membuat berbagai promosi untuk mempertahankan pengguna setia dan pengguna baru. Penelitian ini bertujuan untuk menguji dan menganalisis pengaruh Celebrity Endorsement BTS terhadap Brand Credibility dan Consumer Based-Brand Equity Samsung dan pengaruh Brand Credibility Samsung terhadap Consumer Based-Brand Equity. Penelitian ini menggunakan analisis deskriptif dengan menggunakan kuesioner sebagai alat penelitian. Sampel dalam penelitian ini adalah pengguna ponsel Samsung yang merupakan penggemar boyband BTS. Data penelitian dikumpulkan dengan menyebarkan kuesioner online kepada 100 responden. Untuk analisis dan pengolahan data menggunakan Smart Partial Least Square (SmartPLS) 3. Hasil penelitian menjelaskan bahwa Celebrity Endorsement BTS berpengaruh positif terhadap Samsung Brand Credibility, Samsung Brand Credibility berpengaruh positif terhadap Consumer Based-Brand Equity, dan Celebrity Endorsement BTS tidak berpengaruh terhadap Consumer Based-Brand Equity.